M2b macrophage polarization and its roles in diseases - Wang, Le‐xun; Zhang, Sheng‐xi; Wu, Hui‐juan; Rong, Xiang‐lu; Guo, Jiao (Journal of leukocyte biology, 2019)
Macrophages play an important role in a wide variety of physiologic and pathologic processes. Plasticity and functional polarization are hallmarks of macrophages. Macrophages commonly exist in two distinct subsets: classically activated macrophages (M1) and alternatively activated macrophages (M2). M2b, a subtype of M2 macrophages, has attracted increasing attention over the past decade due to its strong immune‐regulated and anti‐inflammatory effects. A wide variety of stimuli and multiple factors modulate M2b macrophage polarization in vitro and in vivo. M2b macrophages possess both protective and pathogenic roles in various diseases. Understanding the mechanisms of M2b macrophage activation and the modulation of their polarization might provide a great perspective for the design of novel therapeutic strategies. The purpose of this review is to discuss current knowledge of M2b macrophage polarization, the roles of M2b macrophages in a variety of diseases and the stimuli to modulate M2b macrophage polarization. Review outlines the current knowledge of the stimuli of M2b macrophage polarization and the roles of these cells in diseases.